2022
DOI: 10.3390/jpm12050761
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Association between VEGF Polymorphisms and the Risk of Coronary Artery Disease in Koreans

Abstract: Coronary artery disease (CAD), a leading cause of death worldwide, has a complex etiology comprising both traditional risk factors (type 2 diabetes, dyslipidemia, arterial hypertension, and cigarette smoking) and genetic factors. Vascular endothelial growth factor (VEGF) notably contributes to angiogenesis and endothelial homeostasis. However, little is known about the relationship between CAD and VEGF polymorphisms in Koreans. The aim of this study is to investigate the associations of 2 VEGF promoter region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 79 publications
(77 reference statements)
0
1
0
Order By: Relevance
“…For instance, Xia Han et al conducted haplotype analysis and discovered that T–C–T, C–C–C, and C–G–C haplotypes were all genetic susceptibility factors for coronary heart disease (OR: 2.43, 2.77, and 2.33) based on VEGF SNP (−460T/C, −634G/C, and 936C/T) [ 32 ]. Similarly, Eun-Ju Ko et al found that VEGF −1154G>A, −1498T>C, +936C>T, +1451C>T, +1612G>A, +1725G>A haplotypes G–T–T–C–G, G–C–C–A–A, and A–T–C–G–G were strongly correlated with coronary artery disease sensitivity in their populations [ 33 ]. Haplotype analysis between VEGF −2578 C/A, −460T/C, −1154 G/A, and +405 G/C SNP found that haplotype C–T–G–G had a higher risk of endometriosis than haplotype C–C–G–G and A–T–G–G [ 34 ].…”
Section: Resultsmentioning
confidence: 98%
“…For instance, Xia Han et al conducted haplotype analysis and discovered that T–C–T, C–C–C, and C–G–C haplotypes were all genetic susceptibility factors for coronary heart disease (OR: 2.43, 2.77, and 2.33) based on VEGF SNP (−460T/C, −634G/C, and 936C/T) [ 32 ]. Similarly, Eun-Ju Ko et al found that VEGF −1154G>A, −1498T>C, +936C>T, +1451C>T, +1612G>A, +1725G>A haplotypes G–T–T–C–G, G–C–C–A–A, and A–T–C–G–G were strongly correlated with coronary artery disease sensitivity in their populations [ 33 ]. Haplotype analysis between VEGF −2578 C/A, −460T/C, −1154 G/A, and +405 G/C SNP found that haplotype C–T–G–G had a higher risk of endometriosis than haplotype C–C–G–G and A–T–G–G [ 34 ].…”
Section: Resultsmentioning
confidence: 98%
“…In recent decades, the death rate has decreased in places like North America and Western Europe. 24 There is a similar mortality rate among men and women, according to reports on mortality. 25 A study that included 997 women (15% of the study population) also revealed that death rate trends are more positive in women than in men.…”
Section: Epidemiologymentioning
confidence: 90%